2010
DOI: 10.1103/physrevb.81.212404
|View full text |Cite
|
Sign up to set email alerts
|

Dual behavior of antiferromagnetic uncompensated spins in NiFe/IrMn exchange biased bilayers

Abstract: We present a comprehensive study of the exchange bias effect in a model system. Through numerical analysis of the exchange bias and coercive fields as a function of the antiferromagnetic layer thickness we deduce the absolute value of the averaged anisotropy constant of the antiferromagnet. We show that the anisotropy of IrMn exhibits a finite size effect as a function of thickness. The interfacial spin disorder involved in the data analysis is further supported by the observation of the dual behavior of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
(43 reference statements)
3
31
3
Order By: Relevance
“…For instance, in AF/FM bilayers, the onset of EB occurs for a critical AF thickness, which is given by the condition R = (K AF t AF )/J EB ≥1, where the K AF and t AF are the anisotropy and the thickness of the AF, respectively, and J EB is the interfacial coupling constant. This implies that the AF thickness needs to be increased until the AF layer can resist the interfacial torque that acts during the rotation of the ferromagnet 15 . In our case, the thickness and the anisotropy of the HFi layer are held constant; therefore the interfacial coupling has to be decreased by increasing the thickness of the interlayer until the condition above is satisfied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in AF/FM bilayers, the onset of EB occurs for a critical AF thickness, which is given by the condition R = (K AF t AF )/J EB ≥1, where the K AF and t AF are the anisotropy and the thickness of the AF, respectively, and J EB is the interfacial coupling constant. This implies that the AF thickness needs to be increased until the AF layer can resist the interfacial torque that acts during the rotation of the ferromagnet 15 . In our case, the thickness and the anisotropy of the HFi layer are held constant; therefore the interfacial coupling has to be decreased by increasing the thickness of the interlayer until the condition above is satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to be related to the anisotropic domain state of the AF system 12 . Using soft X-ray techniques, the frozen and rotatable spins 12,14,15 were observed in several systems, leading to a deeper understanding of the enhanced coercivity and the origin of the EB for systems with uncompensated AF interfaces.…”
mentioning
confidence: 99%
“…K IrMn at RT varies from 1×10 5 to 5.5×10 5 J/m 3 . [25][26][27][28][29] Then, δ w is estimated to be 4.5 to 10.5 nm. This indicates that planar domain walls cannot form inside IrMn layer when t IrMn is less than 4. in Fig.…”
mentioning
confidence: 99%
“…15,16 In addition to this, it has been observed that the coercivity and the rotatable anisotropy field show maximum values for different AF layer thicknesses. 15,[17][18][19][20][21] FM resonance has been shown to be one of the most successful techniques used to determine the values of the effective fields associated with the magnetic anisotropies in FM thin films and multilayers. [22][23][24][25][26] In addition, FMR linewidth measurements also give accurate information about the magnetic relaxation mechanisms in these systems.…”
Section: Introductionmentioning
confidence: 99%